Malignant acrospiroma of chest and abdominal wall treated with chemotherapy - Anis Bandyopadhyay; Mou Das; Sukumar Jana; Anuradha Das (Wolters Kluwer Medknow Publications, 2013)
Acrospiroma denotes a group of benign ductal tumours of the eccrine sweat glands that may or may not be connected to the skin. Although various eccrine sweat gland tumours including benign acrospiroma are widely reviewed, malignant acrospiroma is rarely reported. Malignant acrospiroma have the propensity to recur locally and metastasizes to regional lymph nodes. The primary treatment is wide local excision with or without lymph node dissection. Local radiation is added in the presence of high risk features to reduce the risk of recurrence. We describe a case of a malignant acrospiroma involving wide areas of chest and abdominal wall with metastases to bilateral axillary lymph nodes in a 47 year old man showing minimal clinical response to combination chemotherapy and paclitaxel.